Football – marketplace icon?. Issue 1 (2nd January 2017) - McDonagh, Pierre
ABSTRACT: Football has always been an important part of consumer culture, in many countries producing a global audience for World Cups and millions of people celebrating annual football competitions. It was once described by iconic Liverpool Football Club (FC) football manager Bill Shankly as follows, "Some people think football is a matter of life and death. I don't like that attitude. I can assure them it is much more serious than that." This marketplace icon contribution puzzles over whether football truly represents a marketplace icon and if so how does this effect the world's most popular sports game? The commentary explores the significance of the beautiful game asking the reader to consider that it is not only a marketplace icon but much more than that, likened here to a "supra socio-cultural phenomenon" which rises above market logic or as Foer argues Football explains the world.